Effect of oral administration of in silico epitope-based SARS-CoV-2 virus with ISCOM adjuvants on increasing the number of NK cells and serum IgG in mice - Irma Nur Sukmawati; Meike Tiya Kusuma; Khoirul Anam; Sumarno Retro Prawiro (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2023)
Background: Vaccines are one of the best solutions to deal with the COVID-19 pandemic. Epitope vaccines can be searched in silico. The selection of in silico epitope-based SARS-CoV-2 which is used as a vaccine candidate must be able to trigger an immune response, such as proteins from the spike (S), envelope (E), membrane (M) in SARS-CoV-2. This study aims to determine the potential for in silico epitope-based SARS-CoV-2 from S, EM, and SEM which is immunogenic, non-toxic, and non-allergenic. And evaluate the immune response by measuring the number of NK cells in the spleen and serum IgG levels in mice. Method: This research was carried out in 2 stages, an in silico exploratory study and an experimental study. The exploratory stage consisted of selecting immunogenic, non-toxic, non-allergic vaccine candidates, molecular docking tests, and epitope conjugation with an adjuvant in the form of ISCOM which was observed with a TEM microscope. The first group was the control, and the second group was given ISCOM. The remaining groups were each given the S, EM, and SEM epitope which had been conjugated with ISCOM and all were given orally. In 5 groups, NK cell levels were measured using a flow cytometer, while IgG levels were measured using Elisa. Research: The results of the in-silico test showed that 3 epitopes of S (FLVLLPLVSSQCVN), E (VNSVLLFLAFVVFLLVTLASS), and M (LYIIKLIFLWLLWPVTLACFV-LAAVY) were immunogenic, non-toxic, and non-allergic. Oral administration of in silico epitope-based SARS-CoV-2 in mice could increase the highest number of NK cells in the administration of S epitope. Meanwhile, the highest serum IgG level was given with the combination of SEM epitope. Conclusion: Oral administration of an in-silico epitope based on SARS-CoV-2 from spike, envelope, and membrane can increase the number of NK cells in the spleen and IgG levels in mice.